2021
DOI: 10.3389/fmicb.2021.736780
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Library Screening Reveals Kaempferol as a Potential Antiviral Agent Against African Swine Fever Virus

Abstract: Naturally occurring plant flavonoids are a promising class of antiviral agents to inhibit African swine fever virus (ASFV), which causes highly fatal disease in pigs and is a major threat to the swine industry. Currently known flavonoids with anti-ASFV activity demonstrate a wide range of antiviral mechanisms, which motivates exploration of new antiviral candidates within this class. The objective of this study was to determine whether other flavonoids may significantly inhibit ASFV infection in vitro. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
(65 reference statements)
0
22
0
Order By: Relevance
“…Luteolin could exert its antiviral activity through CoV proteins during viral infection. Amentoflavone, a prototype of isoginkgetin, possesses a broad-spectrum antiviral activity against various viruses [ 24 , 47 , 48 ]. However, our results showed that a high concentration of amentoflavone was required to inhibit FIPV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin could exert its antiviral activity through CoV proteins during viral infection. Amentoflavone, a prototype of isoginkgetin, possesses a broad-spectrum antiviral activity against various viruses [ 24 , 47 , 48 ]. However, our results showed that a high concentration of amentoflavone was required to inhibit FIPV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Siebold ( Fang et al, 2008 ; Singla et al, 2021 ), Vachellia nilotica (L.) P.J.H.Hurter and Mabb. ( Singh et al, 2008 ), etc, with multiple therapeutic potential, including but not limited to antiproliferative ( Park et al, 2021 ), antiviral ( Arabyan et al, 2021 ), hepatoprotective ( Alshehri et al, 2021 ), antioxidant ( Sharma et al, 2021 ), etc. Similarly, chlorogenic acid had been reported from multiple resources, including Cocos nucifera L. ( Bankar et al, 2011 ), apple fruit ( Hulme, 1953 ), Neolamarckia cadamba (Roxb.)…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids such as kaempferol, which is known to have pharmacological properties-including anti-inflammatory and anticancer effects [17,18]  are abundant in plants [19]. Kaempferol also inhibits infection of African swine fever virus, Influenza virus, Japanese encephalitis virus, and Herpes simplex virus [20][21][22][23]. Thus, in this study, we investigated the inhibitory effects of kaempferol on VZV infection and its mechanism of action in vitro.…”
Section: Kaempferol Inhibits Vzv Replicationmentioning
confidence: 99%
“…Furthermore, kaempferol inhibits Japanese encephalitis virus (JEV) by acting directly on JEV RNA [22] and inhibits the entry and post-entry stages of African swine fever virus. The post-entry stage of the virus life cycle is associated with autophagy induction, and kaempferol cell cycle arrest and impacts autophagic processes [20,29]. VZV infections are suppressed by inhibition of autophagy [30].…”
Section: Kaempferol Is Abundant In Medicinal Plantsmentioning
confidence: 99%